The Role Of Transformational Leadership In Achieving Organizational Commitment Among Workers In Syrian Universities - علي ديب, كندة; عيسى , جميل; صيوح , وائل (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to identify the contribution of transformational leadership in its four dimensions (ideal influence of leadership - inspirational motivation - intellectual arousal - individual consideration) in achieving organizational commitment among workers in Syrian universities. The researcher followed the descriptive approach in his study, and to achieve the objectives of the study, the researcher made a questionnaire that was designed and distributed to an easy sample consisting of (150) respondents, from which (144) were recovered, and (140) questionnaires were valid for analysis, and the research community consisted of the staff of Tishreen University, Hence, the SPSS23 program was relied upon to analyze the available data. The study reached a set of results, the most important of which are: that transformational leadership in its various dimensions contributes to achieving organizational commitment among workers, and the need to take into account the strengthening of organizational commitment among workers in Syrian universities by involving them in the decision-making process.